2022
DOI: 10.1186/s12915-022-01483-0
|View full text |Cite
|
Sign up to set email alerts
|

An IGF1-expressing endometrial stromal cell population is associated with human decidualization

Abstract: Background Decidualization refers to the process of transformation of endometrial stromal fibroblast cells into specialized decidual stromal cells that provide a nutritive and immunoprivileged matrix essential for blastocyst implantation and placental development. Deficiencies in decidualization are associated with a variety of pregnancy disorders, including female infertility, recurrent implantation failure (RIF), and miscarriages. Despite the increasing number of genes reportedly associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 70 publications
3
7
0
Order By: Relevance
“…IGFBP1 expression by control eSCs following cAMP+MPA-induced decidualization was confirmed by confocal microscopy (Figure 1D). IGFBP1 protein was absent without deciduogenic stimulation, and as previously described 30 not all cells express IGFBP1 following cAMP+MPA stimulation. Furthermore, quercetin increased cAMP+MPA-induced IGFBP1 expression by eSCs as determined by confocal microscopy (Figure 1D).…”
Section: Resultssupporting
confidence: 80%
“…IGFBP1 expression by control eSCs following cAMP+MPA-induced decidualization was confirmed by confocal microscopy (Figure 1D). IGFBP1 protein was absent without deciduogenic stimulation, and as previously described 30 not all cells express IGFBP1 following cAMP+MPA stimulation. Furthermore, quercetin increased cAMP+MPA-induced IGFBP1 expression by eSCs as determined by confocal microscopy (Figure 1D).…”
Section: Resultssupporting
confidence: 80%
“…Our results indicated that Id2 , considered as canonical direct transcriptional targets of BMP-SMAD signaling ( Hollnagel et al, 1999 ; Miyazono and Miyazawa, 2002 ), is also regulated by PR. We also confirmed that known P4-responsive genes such as Tgfbr2 ( Holloran et al, 2020 ) and Runx1 ( Dinh et al, 2023 ), as well as decidual markers such as Foxo1 ( Vasquez et al, 2018 ) and Igf1 ( Shi et al, 2022 ), were co-regulated by SMAD1, SMAD5, and PR ( Figure 5C ).…”
Section: Resultssupporting
confidence: 74%
“…Our results indicated that Id2 , considered as canonical direct transcriptional targets of BMP-SMAD signaling 72, 73 is also regulated by PR. We also confirmed that known P4-responsive genes such as Tgfbr2 74 and Runx1 75 , as well as decidual markers such as Foxo1 76 and Igf1 77 , were co-regulated by SMAD1, SMAD5 and PR (Figure 5C).…”
Section: Resultssupporting
confidence: 74%